Novel solid-state compounds of heavy rare-earth (III) picolinates. A pyrolytic study using: TG-DSC-IR, HSM-MS and GC-MS - Nascimento, A. L.C.S. [UNESP]; Ashton, G. P.; Parkes, G. M.B.; Ekawa, B. [UNESP]; Fernandes, R. P. [UNESP]; Carvalho, A. C.S. [UNESP]; Ionashiro, M. [UNESP]; Caires, F. J. [UNESP] (Elsevier, 2019)
Heavy trivalent lanthanides and yttrium picolinates were synthesized by complexation of basic rare-earth metal carbonates with an aqueous solution of picolinic acid. The novel compounds were obtained with the general formula Ln(L)3∙nH2O, where L is picolinate and n = 1.5 H2O (Dy, Ho, Yb, Lu and Y), 2 H2O (Tb and Tm) and 2.5 H2O (Er). The stoichiometry of the complexes was calculated through mass losses found using thermogravimetry (TG), complexometry and elemental analysis (EA). The thermal behavior in oxidative and pyrolytic atmospheres of the compounds was analyzed by simultaneous thermogravimetry - differential scanning calorimetry (TG-DSC). The gaseous products of the pyrolysis were determined throughout by monitoring the evolved species using TG-DSC couple to Fourier transform infrared spectroscopy (TG-DSC-IR), hot-stage microscopy mass spectrometry (HSM-MS), and gas chromatography-mass spectrometry (GC-MS). The obtained results validated mass loss assignments made using the TG curves. However, gaseous product analysis indicates the degradation processes are more complex than the thermoanalytical techniques suggest alone. This study used a GC-MS technique to identify the condensed gaseous products obtained during the second step of thermal degradation of the picolinate complexes. The analysis of the symmetric and asymmetric stretching frequencies of the carboxylate group in the IR spectra showed a monodentate bonding mode. The compounds were obtained in the amorphous state, as indicated by the powder x-ray diffractometry (PXRD) data.
Keywords: evolved gas analysis (EGA); GC-MS; Heavy trivalent lanthanide picolinates; HSM-MS; TG-DSC-IR